Literasi Ekonomi Islam: Potret Pada Alumni IAIN Kerinci - Mursal, Mursal; Fauzi, Muhammad; Ditama, Rezki Agrisa (Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to look at Islamic economics literacy on alumni of FEBI IAIN Kerinci, both in terms of knowledge, understanding and ability to apply attitudes (actions) from Islamic economics material that was studied during college into everyday life. This research uses a qualitative descriptive method, relying on verified data from interviews and observations on alumni of FEBI IAIN Kerinci as the main source, which is analyzed using data reduction, data display and data verification methods. The results of the research show that the Islamic economics literacy on alumni of FEBI IAIN Kerinci shows that some of them have knowledge and understanding of Islamic economics at the Sufficient Literate level, and also some of them also have knowledge and understanding at Less Literate, and even some of them have knowledge and understanding is at Not Literate. This is how it is implemented, it appears that some have been able to apply it in their daily economic activities well, but others are still not able to apply it in their daily economic activities.